A Small Molecule-Screening Pipeline to Evaluate the Therapeutic Potential of 2-Aminoimidazole Molecules Against Clostridium difficile - Thanissery, Rajani; Zeng, Daina; Doyle, Raul G.; Theriot, Casey M. (Frontiers in Microbiology, 2018)
Antibiotics are considered to be the first line of treatment for mild to moderately severe Clostridium difficile infection (CDI) in humans. However, antibiotics are also risk factors for CDI as they decrease colonization resistance against C. difficile by altering the gut microbiota and metabolome. Finding compounds that selectively inhibit different stages of the C. difficile life cycle, while sparing the indigenous gut microbiota is important for the development of alternatives to standard antibiotic treatment. 2-aminoimidazole (2-AI) molecules are known to disrupt bacterial protection mechanisms in antibiotic resistant bacteria such as Pseudomonas aeruginosa, Acinetobacter baumannii, and Staphylococcus aureus, but are yet to be evaluated against C. difficile. A comprehensive small molecule-screening pipeline was developed to investigate how novel small molecules affect different stages of the C. difficile life cycle (growth, toxin, and sporulation) in vitro, and a library of commensal bacteria that are associated with colonization resistance against C. difficile. The initial screening tested the efficacy of eleven 2-AI molecules (compound 1 through 11) against C. difficile R20291 compared to a vancomycin (2 µg/ml) control. Molecules were selected for their ability to inhibit C. difficile growth, toxin activity, and sporulation. Further testing included growth inhibition of other C. difficile strains (CD196, M68, CF5, 630, BI9, M120) belonging to distinct PCR ribotypes, and a commensal panel (B. fragilis, B. thetaiotamicron, C. scindens, C. hylemonae, L. acidophilus, L. gasseri, E. coli, B. longum subsp. Infantis). Three molecules compound 1 and 2, and 3 were microbicidal, whereas compounds 4, 7, 9, and 11 inhibited toxin activity without affecting the growth of C. difficile strains and the commensal microbiota. The antimicrobial and anti-toxin effects of 2-AI molecules need to be further characterized for mode of action and validated in a mouse model of CDI.